ANALYSIS OF WORK SATISFACTION, ORGANIZATIONAL COMMITMENTS, AND WORK ENGAGEMENT EFFFECT TOWARD EMPLOYEE PERFORMANCE IN SHARIA BANKS - Tho'in, Muhammad; Muliasari, Dewi (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
The main objective of this research is to examine the effect of job satisfaction, organizational commitment, and work involvement on the performance of employees at Bank Syariah Mandiri (BSM) in Surakarta. This study uses a quantitative approach and the data used in this study are primary data sourced from questionnaires distributed to BSM employees totaling 60 questionnaires as respondents (according to the number of BSM employees in Surakarta). The sampling method in this study is to use a total sampling technique. Methods of data analysis using descriptive statistics, validity test, reliability test, multiple linear regression analysis test, t test, and R2 test. The results showed that partially job satisfaction variables, organizational commitment variables, and work engagement variables significantly influence employee performance at Bank Syariah Mandiri in Surakarta. Keywords: job satisfaction, organizational commitment, job involvement, employee performance